ChemInform Abstract: Synthesis, Antimicrobial Activity and Molecular Docking of Novel Tetracyclic Scaffolds Incorporating a Flavonoid Framework with Medium Sized Oxygen Heterocycles. Issue 24 (June 2015) - Dongamanti, Ashok; Aamate, Vikas Kumar; Devulapally, Mohan Gandhi; Gundu, Srinivas; Kotni, Meena Kumari; Manga, Vijjulatha; Balasubramanian, Sridhar; Ernala, Prasad
Abstract: 16 Tetracyclic compounds of type (III) are prepared and evaluated for their in vitro antibacterial activity.